Investing in women’s employment essential for economic growth - Jocelyne Sambira (Africa Renewal, 2016)
Magette Wade was in her San Francisco apartment getting ready for the day when she had her “light bulb” moment. Although her beauty cabinet was full of organic and natural products, Ms. Wade says she still reached for the plantbased creams made by herbalists in her native Senegal. In that moment, Tiossano, a luxury skin care company, was born.